THE IMPACT OF THE DECISION-MAKING METHOD IN BUSINESS ACHIEVEMENTS - Canco, Irina (European Scientific Journal, ESJ, 2014)
Whoever dares to learn, finds a way, Whoever renounces to learn, finds a reason! Picasso The environment wherein the business organizations currently operate is increasingly becoming more competitive and the need to face a multitude of challenges arises. Adoption to this environment is conditioned upon finding and using the most analytical efficient forms of managing a business via the use of decision-making analytical methods. The qualitative decision-making highlights the necessity of the scientific and technical capabilities and skills, as well as the creative ideas present in the business environment, in order to provide a sustainable development. The focus of this paper is the aim to consider from the theoretical and practical prospective, the interrelations existing between the decision-making methods used in business and the respective business performance. In this framework, the article entitled: “The impact of the decision-making method in business achievements” poses besides one-another the impacts of the two methods used in the decision-making process. Initially, an overview is made, considering the dimensions of this paper, on some basic concepts of the decision-making theory. Thereafter the theoretical approach, the current decision-making situation and conditioning factors are being is analyzed. The hypothesis is of a simple character, due to the small number of independent variables. The research method is based upon on the ground surveying and the instrument used is face to face interviewing. The aggregate data is analyzed via the non-parametric, statistical analysis, such as the Association Coefficients, Pearson(C) Coefficient, Cuprov(T) Coefficient, Kendall Coefficient. The findings are indispensable as they highlight the necessity of considerable support with efficient programs the human resources development of the decision-making structures.